The "nurse as hero" discourse in the COVID-19 pandemic: A poststructural discourse analysis. (May 2021) - Mohammed, Shan; Peter, Elizabeth; Killackey, Tieghan; Maciver, Jane
Abstract: Background: Nurses have been labelled "heroes" by politicians, the mass media, and the general public to describe their commitment to providing front-line care to people with COVID-19, despite the risks of exposure and lack of clinical resources. Few studies have examined the implications of the hero discourse to nurses' professional, social, and political identities. Objective: To critically examine the effects of the hero discourse on nurses who are contending with the ongoing COVID-19 crisis and to consider the political, social, cultural, and professional impact of this discourse on nursing work. Methods: A poststructural discourse analysis, employing the theoretical ideas of truth, power, knowledge, subjectivity, and normalization, was conducted to explore the mass media's constructions of nurse as hero in the contexts of COVID-19. Media electronic databases were searched between March 1, 2020 to August 1, 2020 to locate newspaper and magazine articles, corporate advertisements, videos, social media postings, and institutional/corporate websites. Setting: Data sources included English language media accounts that originated from Canada, the USA, and the UK. Results: Three main elements of the hero discourse include: 1. Nurses as a "necessary sacrifice" - portraying nurses as selfless, sacrificing, and outstanding moral subjects for practicing on the front-line without adequate protective gear and other clinical resources; 2. Nurses as "model citizens" - positioning nurses as compliant, hardworking, and obedient subjects in contrast to harmful individuals and groups that ignore or resist COVID-19 public health measures. 3. Heroism itself as the reward for nurses - characterizing hero worship as a fitting reward for nurses who were unappreciated pre-pandemic, as opposed to supporting long-term policy change, and highlighting how heroism reconfigures nursing work from the mundane and ordinary to the exciting and impactful. Conclusions: The hero discourse is not a neutral expression of appreciation and sentimentality, but rather a tool employed to accomplish multiple aims such as the normalization of nurses' exposure to risk, the enforcement of model citizenship, and the preservation of existing power relationships that limit the ability of front-line nurses to determine the conditions of their work. Our study has implications for approaching the collective political response of nursing in the ongoing COVID-19 crisis and formalizing the ongoing emotional, psychological, ethical, and practice supports of nurses as the pandemic continues.